Improving use case definition using enterprise communication networks - Luzuriaga, Juan Manuel (2005)
Although researchers noted the importance of effective communication among stakeholders, it continues to be a challenge for requirements engineering. Communication can be considered as a management tool since communication allows organisation’s personnel to produce a cohesive enterprise view. In this paper, we briefly introduce our proposal on using enterprise communication networks to facilitate domain understanding. Then, we illustrate how to take advantage of these networks to improve use case definition.